Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
1
Step-by-step explanation:
(x-h)^2+(y-h)^2=r^2
radius = 7 = 49
h,k = -2,-3
fill in the blanks
Answer:
1. (x + 2)^2 + (y + 3)^2 = 49
Step-by-step explanation:
Circle equation: (x-h)^2 + (y-k)^2 = r^2
(h,k) = (-2,-3)
r = 7
(x+2)^2 + (y+3)^2 = 7^2
(x+2)^2 + (y+3)^2 = 49
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.